2018
DOI: 10.1038/s41598-018-33259-4
|View full text |Cite
|
Sign up to set email alerts
|

Photoacclimation strategies in northeastern Atlantic seagrasses: Integrating responses across plant organizational levels

Abstract: Seagrasses live in highly variable light environments and adjust to these variations by expressing acclimatory responses at different plant organizational levels (meadow, shoot, leaf and chloroplast level). Yet, comparative studies, to identify species’ strategies, and integration of the relative importance of photoacclimatory adjustments at different levels are still missing. The variation in photoacclimatory responses at the chloroplast and leaf level were studied along individual leaves of Cymodocea nodosa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Thalassia hemprichii is less responsive to high light than Halophila ovalis [22], in which the photoprotective mechanisms involve increased dissipation of excess energy and the activity of antioxidant enzymes. Schubert et al [23] found anatomic modifications in seagrass leaves in response to light availability, more pronounced in C. nodosa than in Zostera marina and Zostera noltii. Co-occurring stressors, such as high-temperatures, condition the plants' light use capacity by affecting several metabolic processes, such as electron transport rate [20], carbon acquisition, and fixation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thalassia hemprichii is less responsive to high light than Halophila ovalis [22], in which the photoprotective mechanisms involve increased dissipation of excess energy and the activity of antioxidant enzymes. Schubert et al [23] found anatomic modifications in seagrass leaves in response to light availability, more pronounced in C. nodosa than in Zostera marina and Zostera noltii. Co-occurring stressors, such as high-temperatures, condition the plants' light use capacity by affecting several metabolic processes, such as electron transport rate [20], carbon acquisition, and fixation [21].…”
Section: Introductionmentioning
confidence: 99%
“…The subtle change in carotenoid contents with light intensity can be related to the preservation of heat dissipation mechanisms, as mentioned above, and/or to an optimization of light harvesting in low-light environments ( Silva et al, 2013 ; Davey et al, 2018 ). Changes in pigment contents are often considered as photoacclimatory mechanisms enabling better light absorption ( Ralph et al, 2007 ; Schubert et al, 2018 ). However, the adaptation of seagrasses to the aquatic life, consisting of concentrating the chloroplasts in the leaf epidermis to optimize inorganic carbon acquisition ( Hemminga and Duarte, 2000 ; Enríquez, 2005 ), leads to a strong package effect ( Cummings and Zimmerman, 2003 ; Enríquez, 2005 ; Durako, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, rapid adjustments to a new constant irradiance take place in a matter of days through subcellular photosynthetic changes ( Lambers et al, 2008 ). On the other hand, photoacclimation, i.e., photosynthetic, physiological, and morphological adjustments to light conditions may take weeks to months, and occur from subcellular to plant scale ( McMahon et al, 2013 ; Schubert et al, 2018 ). At shoot scale, an increase in leaf surface or photosynthetic biomass, often approximated by an increase of the above or below-ground biomass ratio, helps maintain carbon balance by decreasing the proportion of non-photosynthetic tissues relative to photosynthetic ones ( Olesen and Sand-Jensen, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our investigation solely focused on the youngest mature ramets as they represent a significant site with a fully developed structure and function. These youngest mature ramets are metabolically active, and they have been widely used in physiological investigations ( Short & Duarte, 2001 ; Collier et al, 2008 ; Park et al, 2016 ; Schubert et al, 2018 ; Rasmusson et al, 2019 ; Nguyen et al, 2020 ). Following the literature mentioned above, we used the third ramet from the growing apex of C. rotundata and T. hemprichii and the second ramet from the growing apex of H. ovalis .…”
Section: Methodsmentioning
confidence: 99%